ANALISIS KINERJA KEUANGAN PT. PEGADAIAN (PERSERO) CABANG BREBES - Agus Sutiyarto (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
ABSTARCT This study aims to analyze the level of financial health in terms of liquidity ratios, profitability, activity, and solvency at PT. Pegadaian (Persero) Brebes Branch based on BUMN Ministerial Decree Number: Kep-100 / MBU / 2002. Analysis tool by taking procedures for assessing the level of financial health, especially only on the financial aspects, where PT Pegadaian (Persero) is classified as a Non-Infrastructure BUMN company. The results showed that PT Pegadaian (Persero) Brebes Branch was declared classified in very healthy conditions in the current ratio of liquidity ratios from 2012 to 2016, amounting to 210.24%. classified in unhealthy conditions in profitability ratios, the ROE ratio is -3.06%. While the ROI ratio is 1.46%. classified in a fairly healthy condition in the activity ratio, the average value of the TATO ratio is 77.00%. and the CP ratio of 110,894 days or 110 days, classified in unhealthy conditions by the ratio of solvency ratios of the average MS to TA ratio of 98.09%.